2011
DOI: 10.1182/blood-2010-04-279539
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant global methylation patterns affect the molecular pathogenesis and prognosis of multiple myeloma

Abstract: We used genome-wide methylation microarrays to analyze differences in CpG methylation patterns in cells relevant to the pathogenesis of myeloma plasma cells (B cells, normal plasma cells, monoclonal gammopathy of undetermined significance [MGUS], presentation myeloma, and plasma cell leukemia). We show that methylation patterns in these cell types are capable of distinguishing nonmalignant from malignant cells and the main reason for this difference is hypomethylation of the genome at the transition from MGUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
228
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(241 citation statements)
references
References 54 publications
9
228
1
3
Order By: Relevance
“…1,4,25,26,29 It has also been described that some of these features are associated with specific phenotypic profiles, 7,30 but in contrast to other hematological malignancies, 31,32 in MM the antigenic profile of malignant cells is not usually taken into account for patient risk stratification. 33 We have recently reported that CD19 expression in MM-PCs is an adverse prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,25,26,29 It has also been described that some of these features are associated with specific phenotypic profiles, 7,30 but in contrast to other hematological malignancies, 31,32 in MM the antigenic profile of malignant cells is not usually taken into account for patient risk stratification. 33 We have recently reported that CD19 expression in MM-PCs is an adverse prognostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, intensive scientific research has unraveled the presence of key genetic, 2,3,25,26 transcriptomic 27,28 and epigenetic 29 features that contribute to understand the pathophysiology of MM, and define patient subgroups with different outcome. 1,4,25,26,29 It has also been described that some of these features are associated with specific phenotypic profiles, 7,30 but in contrast to other hematological malignancies, 31,32 in MM the antigenic profile of malignant cells is not usually taken into account for patient risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, aberrant DNA methylation is an alternative to chromosomal deletion for silencing tumor suppressor genes (Yu et al, 2005). The methylated genes have designated roles in multiple cellular functions, including DNA repair, cell-cycle control, regulation of development, differentiation and apoptosis (Ronchi et al, 1995;Yu et al, 2005;Lin et al, 2011;Meyer et al, 2011;Walker et al, 2011). It has been shown that genomically underrepresented and randomly distributed CpG dinucleotides, even a single CpG dinucleotide, can function as hotspots for aberrant methylation and gene silencing (Santoro et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…58 This translocation leads to a gene-specific hypermethylation signature compared to other cytogenetic sub-groups. 5,93 Other histone modifiers deregulated in myeloma include KDM6A (UTX), a histone demethylase, MLL, KDM6B and HOXA9. 94 Chromatin regulators have the potential to be attractive targets in cancer therapy.…”
Section: Aspect 7 Epigenetic Changesmentioning
confidence: 99%
“…3 While the mechanisms underlying this transformation process generally involve the acquisition of DNA mutations over time, it is becoming increasingly recognized that epigenetic changes play an equally important function. 4,5 This mechanistic approach to treatment is one of the key tenets of modern medicine, where the overall aim is to understand the pathological basis of the disease such that it can be manipulated therapeutically. If this is the case, then the problem of curing myeloma can be viewed simply as an issue of understanding what is underlying the normal behavior of the normal plasma cell which has become deregulated to give rise to myeloma.…”
mentioning
confidence: 99%